Self-Nanoemulsifying Drug Delivery System (SNEDDS): Challenges and Opportunities in Enhancing Drug Solubility - Farhad Aulan Sabillah; Hannie Fitriani; Muhammad Sulaiman Zubair; Yandi Syukri (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
For oral medications, especially those in BCS Classes II and IV, poor aqueous solubility continues to be a significant formulation challenge. This problem restricts dosage consistency, therapeutic efficacy, and bioavailability. A promising method for improving the solubility and absorption of lipophilic drug compounds is the Self-Nanoemulsifying Drug Delivery System (SNEDDS). With ramifications for the pharmaceutical and medical domains, this narrative review attempts to investigate the synthesis, characterization, difficulties, and possible uses of SNEDDS in improving drug solubility. According to the standards of scientific merit, accessibility, and relevance, a total of 25 articles released within the previous five years were included. When SNEDDS meet gastrointestinal fluids, they spontaneously form nanoemulsions, which improves drug solubility. Oil, surfactant, and co-surfactant make up this system, which is optimized according to zeta potential (±30 mV), polydispersity index (<0.3), and particle size (<200 nm). Numerous studies have shown how well it works to enhance the pharmacokinetics and solubility of medications like thymoquinone, rosuvastatin, and curcumin. However, issues with excipient safety, formulation scalability, and long-term stability still exist. SNEDDS offers a versatile and efficient method for enhancing oral drug delivery, especially for nutraceuticals and health supplements. To fully realize its therapeutic and industrial potential, more research involving clinical validation, regulatory harmonization, and quality-by-design approaches is required.